FILLING THE GAP, BETWEEN THE THEORY AND PRACTICE, AND THE HELP OF EDUCATIVE NOVELTIES - Mullai Yllka (European Scientific Journal, ESJ, 2015)
The topic of this study is the gap between theory and practice and also the ways of avoiding it. New educational purposes concerning students, building up an air full of targets, abilities and expressions of research, ability of cooperation and dealing with changes are also the exact abilities that teachers need. The gap between theory and practice is caused by: policymakers seldom ask successful classroom educators for their ideas about creating a modern teaching profession. Despite the importance that historians have placed on teaching and collaboration, this partnership almost does not exist among teachers. The reality is particularly frightening and problematic in Albanian schools. Semi-structured interviews were conducted on 352 teacher candidates. We believe that schools need to embrace the rebels and turn them into leaders reform.The success of student depends on the success of teachers, which is necessary for the success of the society.